STYLISTIC CHANGES AN EXAMPLE OF HARRY POTTER AND THE HALF-BLOOD PRINCE - Inog’omjonova Robiya Rustamjon qizi, (Лучшие интеллектуальные исследования, 2023)
Stylistics encountered in the translation process of the article aimed at revealing the type of transformation. Also, the article, in the course of reading, you will also have some information about the types of transfer of meaning you will be That is, metaphors, metonymy, and synecdoche sufficient explanations and examples are provided. Below is a stylistic change Some examples give a better understanding of this type of change will give.